Don’t Peak Too Early: Evidence for an ACL Injury Prevention Mechanism of the 11+ Program - Haraldur B Sigurðsson; Kristín Briem; Karin Grävare Silbernagel; Lynn Snyder-Mackler (International Journal of Sports Physical Therapy)
# Background